Political Economy of Tertiary Education Investment and Labor Welfare in Indonesia: Impacts on Productivity Growth from the New Order to the Reform Era - Aji, Rizqon Halal Syah (Universitas Pendidikan Ganesha, 2025)
This study aims to examine the role of tertiary education and labour welfare in influencing labour productivity in Indonesia. It checks whether tertiary education, labour welfare and capital production have influence on productivity for the period of 35 years from 1981-2015. These developments of labour productivity need to be seen as part of an evaluation of the role of tertiary education and labour welfare. This research involves the publication of the World Bank to obtain tertiary education registration data as a proxy for education, and GDP as a proxy for labour welfare. Other control variables, capital production, which is set as a proxy for production power, are taken from the publication of APO (Asian Productivity Organization) data. In addition, productivity proxies used are Total Factor Productivity (TFP) which is also sourced from APO. Empirical results with ARDL (Autoregressive Distributed Lag) reveal that the effect of long-term elasticity of tertiary education variables and Capital Production (CP) is significantly positive on labour productivity while labour welfare has a significant negative effect. These findings show that in the long-run tertiary education levels are as important for labour productivity as capital production. Furthermore, this empirical study explains that labour welfare has a significant negative effect on productivity. The government needs to ensure the continuity of tertiary education investment and production capital in order to contribute positively and significantly in the long run, also special attention needs to grant an improvement the welfare of the workforce.